A Feature of Setting Educational Tasks for Younger Students on the Basis of a Differentiated Approach - Akmal Ochilov Eshtemirovich (Researchparks Publishing, 2022)
This article describes the features and methods of presenting educational tasks and assignments to primary school students based on a graded differential approach.